Chapter 17 The Racial Contours of Queer Reproduction - Twine, France Winddance (Taylor & Francis, 2022)
In this chapter, we bring queer theory into dialogue with critical race studies. We ask "How does the literature in queer kinship engage with the issues of race and intersecting inequalities?'' This chapter builds upon the foundational literature in queer family studies. It departs from the foundational literature in the anthropology of reproduction by placing the role that racial hierarchies and racial logics play at the center of analysis. We refer to family forms that do not conform to heteronormative, monoracial models. This chapter also advances debates in anthropology that illuminate the social, cultural, and political imperatives that confer respectability and legitimacy to transgressive family forms. Given the changing legal and global landscape, we offer a nuanced analysis of the ways that queer families employ racial and cultural logics as they engage with technologies in their pathways to parenthood. Finally, our analysis innovates and renovates queer family studies by proving an analysis of the ways that heteronormativity and Whiteness mark all logics of reproduction in the early twenty-first century.